Influence of sawtooth twisted tape on thermal enhancement of heat exchanger tube - Boonsong Samutpraphut; Smith Eiamsa–ard; V. Chuwattanakul; Chinaruk Thianpong; Naoki Maruyama; Masafumi Hirota (Energy Reports, 2022)
This article employs sawtooth twisted tapes to generate swirling flow and interrupted flowing disturbance in order to increase the level of heat transfer rate. The influences of the sawtooth twisted tape (S-TT) on enhanced heat transfer rate, friction factor and aerothermal performance index (API) behaviors are analyzed. The sawtooth twisted tapes (S-TTs) possessing constant pitch/twist ratio (y//W) of 3.0 and six sawtooth angles (α) of 20°, 30°, 40°, 50°, 60°, and 70° are assessed. Considering turbulent flow using air as the testing fluid, experiments were investigated at 6,000 < Re < 20,000 under boundary conditions of constant heat flux. According to the experimental findings, sawtooth twisted tape (S-TT) improves heat transfer rate and raises pressure loss with varying rates based on sawtooth angles (α). With the sawtooth twisted tape (S-TT) and 70° sawtooth angles, the optimum API of 1.33 is attained, while Nusselt number and friction factor are 32 and 0.135 at Re = 6,000. The recommended sawtooth twisted tape (S-TT) yields a highest Nusselt number of 78, which is 1.6 times greater than the typical twisted tape (TT) and 1.1 times greater than the plain tube. The combination of the TT and sawtooth patterns can be beneficial in terms of boosting heat transfer rate and API relating coupling of swirling flow and interrupted flowing disruption effects since the sawtooth twisted tape (S-TT) offers superior performance than the TT. Additionally, the heat exchanger tubes fitted with sawtooth twisted tape (S-TT) at sawtooth angles (α) of 20°, 30°, 40°, 50°, 60°, and 70° gain greater Nusselt number than the plain tube up to 158.3%, 162.2%, 166.1%, 171.7%, 179.7% and 186.2%, respectively.
Keywords: Heat Transfer Mechanisms; Nanofluid Flow and Heat Transfer; Fluid Dynamics and Turbulent Flows